Twelve tips for improvement-oriented evaluation of competency-based medical education. (3rd March 2020) - Oandasan, Ivy; Martin, Liz; McGuire, Melissa; Zorzi, Rochelle
Abstract: The shift to competency-based medical education (CBME) requires a new approach to program evaluation. CBME implementers need to embed evaluation in their programs to ensure their CBME adapts to the changing demands of the healthcare system. This 12 tips paper proposes that those advancing CBME use an improvement-oriented, utilization-focused approach to program evaluation. This will yield information that can help CBME implementers to continually examine the context, process and early outcomes of their programs. The paper uses examples from the College of Family Physicians of Canada's (CFPC's) evaluation of the implementation of the Triple C Competency-based curriculum in family medicine residency programs across Canada. These practical tips will be useful to medical educators looking to integrate evaluation into their CBME programs and to those considering other curriculum reform in health professions education.